Composition and Structure of Tiwoho Mangrove Vegetation at Bunaken National Parkional Park (Komposisi Dan Struktur Vegetasi Mangrove Tiwoho di Kawasan Taman Nasional Bunaken) - Supratman Tabba; Nurlita Indah Wahyuni; Hendra Susanto Mokodompit (Balai Penerapan Standar Instrumen Lingkungan Hidup dan Kehutanan (BPPLHK)Manado, 2015)
Tiwoho mangrove forest islocated in north coast of North Sulawesi province.This area functions as life buffer system for community and sustainability of Bunaken National Park. Due to the important and strategic roles of mangrove in protection and ecological functions, therefore, it is needed to know scientific information about mangrove population dynamics. This research aims to know the vegetation composition and structure vegetation of Tiwoho mangrove forest. Data collection used 20x20 m sample plots that were sistematically laid from the sea to the land side up to the highest tidal line. Distance between plots along 25 m. Results showed that at tree level Sonneratia alba had the highest Important Value Index (IVI) of 206,88 % and Brugueira sp of 46,06 %. Although Rhizopora apiculata value is lower than Brugueira sp. But the values of relative frequency of these species are almost similar. It means that both species are frequently found in observation plots. Rhizophora apiculata dominate at pole and sapling levels, but frequency of occurance this species is lower than Brugueira sp in pole level.